2021
DOI: 10.7150/thno.49426
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 1 receptor attenuates early brain injury following subarachnoid hemorrhage by controlling mitochondrial metabolism via AMPK/SIRT1/PGC-1α pathway in rats

Abstract: Mitochondria-mediated oxidative stress and apoptosis contribute greatly to early brain injury (EBI) following subarachnoid hemorrhage (SAH). This study hypothesized that activation of melanocortin 1 receptor (MC1R), using BMS-470539, attenuates EBI by controlling mitochondrial metabolism after SAH. Methods: We utilized BMS-470539, MSG-606, selisistat, and PGC-1α to verify the neuroprotective effects of MC1R. We evaluated short- and long-term neurobehavior after SAH. Western blotting, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 38 publications
5
62
0
1
Order By: Relevance
“…As a promising route of administration for CNS targeting, intranasal drug administration has several advantages, including bypassing the blood-brain barrier, targeting the brain directly, shorter time to onset of effect, and higher bioavailability due to avoidance of hepatic first-pass metabolism [ 39 , 40 ]. Previous studies and our data showed that BMS-470539 administration 1 h after SAH or HI via the intranasal pathway exerts neuroprotective effects in the SAH and HIE rat models [ 20 , 24 , 26 ]. Based on the above studies, BMS-470539 was also administered intranasally at 1 h after HI induction in the present study.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…As a promising route of administration for CNS targeting, intranasal drug administration has several advantages, including bypassing the blood-brain barrier, targeting the brain directly, shorter time to onset of effect, and higher bioavailability due to avoidance of hepatic first-pass metabolism [ 39 , 40 ]. Previous studies and our data showed that BMS-470539 administration 1 h after SAH or HI via the intranasal pathway exerts neuroprotective effects in the SAH and HIE rat models [ 20 , 24 , 26 ]. Based on the above studies, BMS-470539 was also administered intranasally at 1 h after HI induction in the present study.…”
Section: Methodssupporting
confidence: 52%
“…MC1R activation also exerted anti-inflammatory, antiapoptotic, and neuroprotective effects in a mice model of experimental traumatic brain injury [ 22 ]. As a synthesized small-molecule and specific selective agonist of MC1R, 1-[1-(3-methyl-L-histidyl-O-methyl-D-tyrosyl)-4-phenyl-4-piperidinyl]-1-butanone (BMS-470539) has been shown to attenuate early brain injury (EBI) following subarachnoid hemorrhage (SAH) by inhibiting oxidative stress, neuronal apoptosis, and mitochondrial fission via MC1R signaling [ 23 , 24 ]. By binding with MC1R, BMS-470539 suppressed lipopolysaccharide- (LPS-) induced inflammatory responses and delayed neutrophil apoptosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…After SAH, exhibiting aberrant redox hemostasis, the production of oxidants mainly comes from the disruption of mitochondria ( Yan et al, 2015 ; Fan et al, 2021 ; Xu W. et al, 2021 ), extravascular hemolyzed blood ( Vecchione et al, 2009 ; Deng et al, 2018 ), and enzymatic sources of free radicals ( Sies et al, 2017 ; Yang et al, 2017 ; Sies and Jones, 2020 ). Intrinsic antioxidant activity can be exhausted by excessive free radicals, resulting in lipid peroxidation, protein breakdown, and DNA damage.…”
Section: Oxidative Stress In Subarachnoid Hemorrhagementioning
confidence: 99%
“…The mechanisms for ROS generated by mitochondria are under the consensus that the production of ROS is maximal when the ingredients of the electron transport chains (ETCs) are superlatively impaired ( Murphy et al, 1999 ; Moro et al, 2005 ). Particularly interacting with autophagy and apoptosis, activation of autophagic pathways attenuates EBI after SAH in rats ( Jing et al, 2012 ; Shi et al, 2020 ; Xu W. et al, 2021 ). Among the mounts of antioxidant agents, docosahexaenoic acid (DHA), the so-called omega-3 fatty acid, reduces OS through enhancing mitochondrial dynamics in EBI ( Zhang T. et al, 2018 ).…”
Section: Oxidative Stress In Early Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation